Implantes pós exodônticos em área estética – controle de um ano - Aur Junior, Roberto Jorge (2016)
Rehabilitation with implants is safe and predictable procedure. However, the treatment time is still a limiting factor for patient satisfaction. The tooth extraction and immediate implant insertion has been used and has many advantages, especially in relation to maintaining aesthetic and marginal peri-implant bone loss. The aim of the study was to evaluate the clinical efficacy and volumetric changes in bone level using computed tomography unit rehabilitations in previous aesthetic areas after post exodontics implant and immediate loading. The evaluated were: size of the implant insertion torque, tomographic peri-implant bone change, prosthetic complications and survival of the implant. The first CT scan was performed immediately after surgery (T0) and the second after a year of rehabilitation (T1). Ten patients were included in this study and a total of 10 implants placed in alveolus of the maxillary central incisors immediately without minimally invasive flapless extraction. The space formed between the alveolar wall and the implant surface were filled with bovine bone mineralization. All implants placed presented cone Morse connection, the average length was 15.4 mm and 3.5 mm in diameter. The average insertion torque was 60 N. There was no loss of the implant. The mean reduction (T1-T0) the horizontal distance between the width of the implant surface and the inside of the buccal bone (S - CI) was 0.347 (35%), with a statistically significant difference (p = 0.031250) the horizontal distance across the width of the implant surface and the outside of the vestibular bone (Y - CB) was 2.53 (25%), the average of the vertical distance between the center of the implant and the top of the crest of bone (CR) was 4.26 (43%) and the average thickness of the vestibular bone 0.23 (2%). The results demonstrate the maintenance of the peri-implant tissues, maintenance of interdental papilla, no inflammation and bone loss and adequate aesthetic evaluation after 12 months. It is concluded that post exodontias implants subjected to immediate loading unit in previous edentulous regions approach is predictable with high survival rate of the implant and promotes the maintenance of buccal bone wall